2023
DOI: 10.3389/fphys.2023.1128250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unilateral training and bilateral training on physical performance: A meta-analysis

Abstract: Background: In Unilateral (UNI) exercises are more effective than bilateral (BI) exercises in improving athletic performance is debatable.Objectives: this meta-analysis investigated the effects of UNI and BI exercises on different effect indicators of jump ability, sprint ability, maximal force, change of direction ability, and balance ability.Data Sources: PubMed, Google Scholar, Web of science, CNKI, Proquest, Wan Fang Data.Study Eligibility Criteria: To be eligible for inclusion in the meta-analysis, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 91 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…It is worth noting that young players who want to improve their COD ability should be introduced to this type of training in their middle peak height velocity maturation stage (approximately 13–15.9 years old) because this is when the development of SSC capabilities start accelerating (7). Furthermore, although unilateral training may be more specific to COD actions (89), previous studies found that bilateral training was more effective than unilateral training for improving COD actions at 50° cut-off (2). This might be explained by the fact that, even though COD actions are generally unilateral, athletes often use an asymmetric bilateral strategy during large COD angles.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that young players who want to improve their COD ability should be introduced to this type of training in their middle peak height velocity maturation stage (approximately 13–15.9 years old) because this is when the development of SSC capabilities start accelerating (7). Furthermore, although unilateral training may be more specific to COD actions (89), previous studies found that bilateral training was more effective than unilateral training for improving COD actions at 50° cut-off (2). This might be explained by the fact that, even though COD actions are generally unilateral, athletes often use an asymmetric bilateral strategy during large COD angles.…”
Section: Discussionmentioning
confidence: 99%
“…For this age cohort, exercise prescription should take account into both interventional efficacy and exercise safety. For example, while unilateral exercises or strength training on unstable surfaces are more effective in improving balance than bilateral exercises or training on stable surfaces ( 10 , 11 ), these exercises are neither viable nor safe for vast majority of aging individuals. Given this consideration, low-aerobic dancing and Taijiquan are valuable in reducing the risk of falling in older persons ( 12 ).…”
Section: Introductionmentioning
confidence: 99%